Sensitivity of UV Erythemal Radiation to Total Ozone Changes under Different Sky Conditions: Results for Granada, Spain. (4th November 2015) - Antón, Manuel; Cazorla, Alberto; Mateos, David; Costa, Maria J.; Olmo, Francisco J.; Alados‐Arboledas, Lucas
Abstract: This study focuses on the analysis of the sensitivity of UV erythemal radiation (UVER) to variations in the total ozone column (TOC) under different sky conditions at Granada (southeastern Spain). The sensitivity is studied both in relative terms by means of the Radiation Amplification Factor (RAF) and in absolute terms using the Ozone Efficiency (OE). These two variables are determined for diverse sky conditions characterized by the cloud cover information given by a sky camera (in oktas) and the cloud optical depth (COD) estimated from global solar radiation measurements. As expected, in absolute terms, the TOC variations cause substantially smaller UVER changes during completely overcast situations than during cloud‐free cases. For instance, the OE (SZA = 30°, TOC = 290 DU) decreases from 0.68 mW m −2 per unit of TOC (0 oktas) to 0.50 mW m −2 per unit of TOC (8 oktas). However, the opposite is observed when the analysis is performed in relative terms. Thus, the RAF (determined for SZA cases below 80°) increases from 1.1 for cloud‐free cases (0 oktas) to 1.4 for completely overcast situations (8 oktas). This opposite behavior is also found when both RAF and OE are analyzed as functions of COD. Thus, while the OE strongly decreases with increasing COD, the RAF increases as COD increases. Abstract : The analysis of the sensitivity of UV erythemal radiation (UVER) to total ozone changes during different sky conditions differs if the analysis is performed in relative terms (from the RAF) or in absolute terms (from the OE). Both RAF and OE exhibit a great dependence on the cloud optical depth (COD) during overcast conditions, but with opposite sign: while RAF increases with increasing COD, the OE substantially reduces its value as COD increases. To sum up, the UVER sensitivity to ozone changes is strongly affected by the sky conditions related to the cloud cover.